Application of Quantum Dot nanocrystal in Luminescent solar concentrators - Bakhoda, S. (Institute of Physics Publishing, 2018)
The basic design of luminescent solar concentrator is a transparent plate doped with an appropriate luminescent material (organic dyes, quantum dots), which is able to absorb sunlight (direct and diffuse), and then guides photons produced by photoluminescence to its narrow edges where they are converted by photovoltaic cells. Unfortunately, LSCs have suffered from numerous efficiency losses. Therefore, new luminescent species and novel approaches are needed for its practical application. This paper deals with investigation of nonhazardous, environmental friendly luminescent species include CuInS2/ZnS core/shell QDs. The CuInS2/ZnS QDs possess advantages of Stocks shift as large as more than 130 nm and high photoluminescence quantum yield of 80. The paper presents the effect of large stock shift CuInS2/ZnS QDs on reducing the reabsorption losses in LSC by using experimental investigation. The LSC sheets were fabricated by dispersing CuInS2/ZnS QDs particles in a polymethylmethacrylate waveguide. A series of LSCs (dimension 4.0 cm 3.0 cm 0.3cm) with different CuInS2/ZnS QDs particles concentration (0.015 and 0.03 wt.) were fabricated and their optical properties (absorptions/emissions) were characterized. The results show that the CuInS2/ZnS QDs-LSC provides a promising way for the reduction of reabsorption losses in LSCs. Â© Published under licence by IOP Publishing Ltd.